Strategi Pengembangan Obyek Wisata Air Terjun Coban Binangun (Studi Penelitian Di Desa Plintahan, Kecamatan Pandaan, Kabupaten Pasuruan) - Shafa Mutiara; Hendra Sukmana (STISIPOL Raja Haji, 2026)
The main problem in this research is the absence of a comprehensive and structured development strategy for the Coban Binangun Waterfall Tourism Object in Plintahan Village, Pandaan District, Pasuruan Regency. This study aims to analyze the development strategy of the destination using the theoretical framework of strategy according to Kooten in Salusu (2006:104-105), which includes four indicators: organizational strategy, program strategy, resource strategy, and institutional strategy. This research uses a descriptive qualitative method with a case study approach through in-depth interviews, field observations, and documentation. The results of the study indicate that tourism management is carried out independently by the community through the Pokja and Pokdarwis, but is still weak in the aspects of legality and organizational structure. Program strategies are evident through simple promotions and community empowerment, but they are not yet based on long-term planning. Resource strategies still rely on entrance tickets and local businesses without a formal financial reporting system. Institutional collaboration is limited to the Fisheries Service and is not directly linked to tourism development. This research underscores the importance of strengthening formal institutions and cross-sectoral strategic planning to achieve sustainable and professional tourism management.